Myelin oligodendrocyte glycoprotein induces incomplete tolerance of CD4+ T cells specific for both a myelin and a neuronal self‐antigen in mice. Issue 9 (21st July 2016) - Lucca, Liliana E.; Axisa, Pierre‐Paul; Aloulou, Meryem; Perals, Corine; Ramadan, Abdulraouf; Rufas, Pierre; Kyewski, Bruno; Derbinski, Jens; Fazilleau, Nicolas; Mars, Lennart T.; Liblau, Roland S.
Abstract : In the absence of Myelin oligodendrocyte glycoprotein (MOG), CD4 T cells are not tolerized leading to increased Teff/Treg ratio, and enhanced inflammatory response in MOG −/− NF‐M −/− animals. Absence of such tolerization results in increased encephalitogenic properties. Abstract : T‐cell polyspecificity, predicting that individual T cells recognize a continuum of related ligands, implies that multiple antigens can tolerize T cells specific for a given self‐antigen. We previously showed in C57BL/6 mice that part of the CD4 + T‐cell repertoire specific for myelin oligodendrocyte glycoprotein (MOG) 35–55 also recognizes the neuronal antigen neurofilament medium (NF‐M) 15–35. Such bi‐specific CD4 + T cells are frequent and produce inflammatory cytokines after stimulation. Since T cells recognizing two self‐antigens would be expected to be tolerized more efficiently, this finding prompted us to study how polyspecificity impacts tolerance. We found that similar to MOG, NF‐M is expressed in the thymus by medullary thymic epithelial cells, a tolerogenic population. Nevertheless, the frequency, phenotype, and capacity to transfer experimental autoimmune encephalomyelitis (EAE) of MOG35‐55 ‐reactive CD4 + T cells were increased in MOG‐deficient but not in NF‐M‐deficient mice. We found that presentation of NF‐M15‐35 by I‐A b on dendritic cells is of short duration, suggesting unstable MHC class II binding. Consistently, introducing an MHC‐anchoring residue into NF‐M15‐35 (NF‐M15‐35 T20Y) increased its immunogenicity, activating a repertoire able to induce EAE. Our results show that in C57BL/6 mice bi‐specific encephalitogenic T cells manage to escape tolerization due to inefficient exposure to two self‐antigens.